(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The effect of pre-cooling and waxing of three ‘Galia’ cultivarswas evaluated with regard to fruit quality and shelf-life at 18 ± 1°C and85%- 90% relative humidity. Pre-cooling and/or waxing reduced moistureloss, delayed fruit ripening, maintained quality and extended shelf-life ofthe three cultivars. Pre-cooling and/or waxing delayed the onset of theclimacteric peak, rind color development, fruit softening and TSSaccumulation by one to four days. Weight loss was reduced by an averageof 6.5% in the pre-cooled, 15.8% in the waxed and 27.4% in the pre-cooled and waxed fruits